PENGEMBANGAN TEPUNG IKAN PATIN DAN BAYAM SEBAGAI BAHAN SUBTITUSI BISKUIT UNTUK FINGER FOOD PADA BALITA - Hapsari, Lolita Tasha; Sadiman, Sadiman; Triwijayanti, Yoga Tri (SINERGI : Jurnal Riset Ilmiah, 2025)
Anemia is a serious global public health problem that primarily affects children, girls and adolescent women who are menstruating, as well as pregnant and postpartum women. The prevalence of anemia in pregnant women in the world is estimated at 37%. Based on the results of the Basic Health Research (Riskesdas) in 2018, the prevalence of pregnant women with anemia was 48.9%. According to data from the Lampung Provincial Health Office in 2022, pregnant women experience anemia with a presentation showing a figure of 5.5%. While in Metro City, the prevalence of anemia in pregnant women is 11.4% with the highest anemia at the Ganjar Agung Health Center, Metro City with a percentage of 29.7%. This type of research is quantitative research with a Cross Sectional design. Data collection by looking at medical records. the number of samples needed in this study is 53 respondents. The sampling technique used in this study is simple random sampling. Data analysis uses bivariate analysis with the chi square test at α = 0.05. The results of the Chi Square test analysis of pregnancy spacing with the incidence of anemia were obtained (p-value 0.001) meaning that there is a significant relationship between pregnancy spacing and the incidence of anemia, the results of the parity test with the incidence of anemia were obtained (p-value 0.282) meaning that there is no significant relationship between parity and the incidence of anemia. The conclusion of this study is that there is a significant relationship between pregnancy spacing and the incidence of anemia in pregnant women in the third trimester. There is no significant relationship between parity and the incidence of anemia in pregnant women in the third trimester. Researchers expect health workers and Posyandu Cadres to be able to improve Ante Natal Care, one of which is Hb examination and provision of Fe tablets for pregnant women. Conducting education on safe pregnancy spacing and childbirth.